Available phosphorus as a reproductive performance enhancer for female Nile tilapia - Carvalho, Pedro Luiz Pucci Figueiredo [UNESP]; Koch, João Fernando Albers [UNESP]; Cintra, Felipe Tenório [UNESP]; Fernandes Júnior, Ademir Calvo [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Barros, Margarida Maria [UNESP]; Padilha, Pedro de Magalhães [UNESP]; Pezzato, Luiz Edivaldo [UNESP] (Elsevier, 2018)
This study was conducted to evaluate the effects of dietary available phosphorus (AP) on reproductive performance and bone mineralization of Nile tilapia (Oreochromis niloticus) female broodfish. Four isonitrogenous (35% crude protein), isocaloric (18 MJ crude energy) diets were formulated to contain 1.1, 2.8, 4.9, and 6.7 g kg− 1 AP. The diets were fed to four groups of adult Nile tilapia (176.9 ± 2.6 g average body weight), 3 males and 9 females per aquarium, at 1% of their biomass for 26 weeks. Spawning performance, including spawning frequency (SF), total eggs spawned per fish (TEF), inter spawning intervals (ISI), absolute fecundity (AF), and relative fecundity (RF) significantly improved with increasing dietary AP up to 6.7 g kg− 1. Based on the polynomial regression analysis of the SF, AF, and RF, the optimum dietary supplementation level of AP was determined to be 6.1, 6.5, and 6.1 g kg− 1 diet, respectively. Eggs produced from broodstock fed 6.7 g kg− 1 AP exhibited significantly higher hatchability than at other dietary AP levels. However, there were no differences in weight, diameter, and calcium and phosphorus composition of eggs produced by tilapia fed the experimental diets (P > 0.05). Bone volume and densitometry also significantly improved with increasing dietary AP up to 6.7 g kg− 1. In conclusion, Nile tilapia were responsive to dietary available phosphorus supplementation with fish fed 6.5 g kg− 1 AP showing significantly enhanced spawning performance and bone mineralization.
Keywords: Available phosphorus; Bone densitometry; Broodstock nutrition; Computed tomography; Macro minerals; Oreochromis niloticus; Spawning